2007
DOI: 10.1002/jbm.a.31636
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pulse repetition rate of Er:YAG laser and dentin depth on tensile bond strength of dentin–resin interface

Abstract: The study evaluated the in vitro influence of pulse-repetition rate of Er:YAG laser and dentin depth on tensile bond strength of dentin-resin interface. Dentin surfaces of buccal or lingual surfaces from human third molars were submitted to tensile test in different depths (superficial, 1.0 and 1.5 mm) of the same dental area, using the same sample. Surface treatments were acid conditioning solely (control) and Er:YAG laser irradiation (80 mJ) followed by acid conditioning, with different pulse-repetition rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Other investigations also concluded that bond strength of teeth treated with laser irradiation before bonding was weaker than that of teeth in the control group. 5,28,36 Previous studies on teeth conditioned by laser treatment confirm the results of our study. The control groups treated conventionally with adhesive systems attained the highest bond strengths.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Other investigations also concluded that bond strength of teeth treated with laser irradiation before bonding was weaker than that of teeth in the control group. 5,28,36 Previous studies on teeth conditioned by laser treatment confirm the results of our study. The control groups treated conventionally with adhesive systems attained the highest bond strengths.…”
Section: Discussionsupporting
confidence: 93%
“…Subsequently, all samples were exposed to a thermocycling device (Willytech Thermocycler V.2.8, Haake, Munich, Germany). Thermocycling consisted of 5000 cycles in water between 5 C and 55 C, starting after storage in water at 37 C for 24 h as an accelerated aging test, which corresponded approximately to 6 months of functioning in vivo.…”
Section: Laser Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36][37] The amount of tissue removed is thought to increase in proportion to the Er:YAG laser energy. However, with increased ablation efficiency, the dentin microstructure may be affected by the thermal effect and the resulting surface may vary from a white spot to charring, fusion, roughening, melting, recrystallization, cracking, and both de/remineralization and deproteinization.…”
Section: Discussionmentioning
confidence: 99%
“…The literature available on the Er:YAG laser still presents varying parameters of energy settings, and, besides the fact that little is known about the effect of Er:YAG laser irradiation on different dentin depths [33,34], there are divergent results as well.…”
Section: Introductionmentioning
confidence: 99%